Effects of four different adjuvants separately combined with Aeromonas veronii inactivated vaccine on haematoimmunological state, enzymatic activity, inflammatory response and disease resistance in crucian carp. Issue 120 (January 2022) - Song, Haichao; Zhang, Siqi; Yang, Bintong; Liu, Yanhui; Kang, Yuanhuan; Li, Ying; Qian, Aidong; Yuan, Zhonghua; Cong, Bo; Shan, Xiaofeng
Abstract: The purpose of the current study was to explore the immunomodulatory effects of different adjuvants combined with inactivated vaccines under Aeromonas veronii TH0426 infection in crucian carp. This study explored the best conditions for A. veronii as an inactivated vaccine, and included an animal safety test. Furthermore, we expressed the flagellin FlaA of the A. veronii TH0426 strain for use as an adjuvant supplemented in the diet. Crucian carp were fed 12 different experimental diets for 35 days, including the administration of 10 different adjuvants and inactivated vaccine combinations (50% aluminum hydroxide gel and inactivated vaccine combination, and inactivated vaccine with 20%, 30%, or 50% glucan, astragalus polysaccharide or flagellin), inactivated vaccine alone, and PBS control without adjuvant and inactivated vaccine. After the 42 day feeding trials, the fish were challenged with A. veronii TH0426, and the survival rate over 14 days was recorded. In addition, flagellin FlaA can be expressed normally in large amounts. All experimental groups produced higher levels of IgM serum titres than the control group in the different feeding cycles. Moreover, the activity of serum ACP, AKP, SOD, and LZM, and the expression of inflammatory factors were significantly increased in the experimental groups compared with the control group. The results of qRT-PCR analysis showed that the transcription levels of the IL-10, IL-1β, IFN-γ and TNF-α genes in heart, liver, spleen and kidney tissues were significantly enhanced by adjuvant treatment, indicating that the addition of adjuvants can significantly promote the body's inflammatory response. In addition, the phagocytic activity of leukocytes in each adjuvant treated group was significantly enhanced compared to that in the groups without adjuvant. After the A. veronii challenge, the survival rate of all adjuvant-treated groups was significantly higher than that of the control group, and the 50% flagellin adjuvant group had the highest rate of 78.37%. Overall, our findings strongly indicate that adjuvants not only significantly improve the body's immunity, but also exhibit a strong anti-infection ability. Importantly, this work provides a new perspective for the prevention and control of aquaculture diseases. Highlights: Flagellin can be expressed normally in large quantities and used as an adjuvant. Adjuvants can significantly enhance the body's non-specific immune. Adjuvants can promote the body's pro-inflammatory response of and enhance immunity. Adjuvants can significantly enhance the disease resistance of crucian carp.